DEVELOPMENT OF A MARKETING STRATEGY BASED ON THE ETHNOMETRIC APPROACH - VASYLYSHYNA, Liubov; YAHELSKA, Kateryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article considers the theoretical and methodological aspects of using the ethnometric approach in marketing activities. The close connection between ethnometry and marketing strategy in the conditions of sociocultural differentiation of the marketing environment is substantiated, which is expressed in the fact that ethnometric studies allow a deeper understanding of cultural features and preferences of different consumers. This created the prerequisites for identifying and understanding the basic cultural parameters that serve as the basis for the development of effective marketing strategies. The main foreign and domestic concepts were studied and the existing theories based on ethnometric studies were summarized and the relationships between them were substantiated. Relationships between ethnometric parameters and the development of marketing strategies are revealed through the consideration of cultural influences on consumers. This approach allows companies to effectively respond to socio-cultural differences and individualize their strategies to best meet the needs of different cultural groups. The basic cultural values that exert the greatest influence on the marketing strategy are analyzed. The basic socio-cultural differences and socio-cultural interactions that take place in the marketing activities of domestic companies are determined. A list of universal cultural values of the consumer, adapted to the global marketing environment, which create the basis for choosing a marketing strategy, is offered. An integrated combination with marketing strategies will allow companies to remain relevant in different cultural environments.